ADVANCE REVIEW ON NUTRITIONAL PHYTOCHEMICAL, PHARMACOLOGICAL AND ANTIMICROBIAL PROPERTIES OF CHILI - Pundir, *Reena; Rani, Ruby; Tyagi, Shivi; Pundir, Poonam (International Journal of Ayurveda and Pharma Research, 2016)
India is the world's largest producer, consumer and exporter of chili peppers. It is one of the important commercial crops and a major constituent of Indian diet. It has green color and attain red color on ripening. Chili peppers produces alkaloid compound, capsaicinoids, responsible for the hotness. Chili also contain carotenoids, phenols, foliates and oxidative product which show many biological activities in the human body. It is a good source of minerals like iron, magnesium and potassium, vitamins like A, C, B, E and P and dietary fibers. The nutrient values of Chili depend upon the variety and their stages of maturity. Chili has nutritional values, antimicrobial and pharmacological properties. Chili have many biochemical and pharmacological properties like antioxidants, anti-inflammatory, antiallergenic and anti-carcinogenic. Chili is used in the pharmaceutical industry because of its pharmacological properties. Chili plays important role to increase immunity, anti-ulcer, analgesic, anti-inflammatory, and anti-hemorrhoid agent. The extracts of chilli are used to alleviating the pain of arthritis, headaches, burns and neuralgia. It have the power to boost immune system and lower cholesterol, effective in heart disorders. This is the advance study to made a review of chili focusing mainly on its nutritional phytochemical, pharmacological and antimicrobial and clinical uses.